Faith in African lived Christianity : bridging anthropological and theological perspectives - Lauterbach, Karen; Vähäkangas, Mika (Global Pentecostal and charismatic studies, 2019)
"Faith in African Lived Christianity - Bridging Anthropological and Theological Perspectives offers a comprehensive, empirically rich and interdisciplinary approach to the study of faith in African Christianity. The book brings together anthropology and theology in the study of how faith and religious experiences shape the understanding of social life in Africa. The volume is a collection of chapters by prominent Africanist theologians, anthropologists and social scientists, who take people's faith as their starting point and analyze it in a contextually sensitive way. It covers discussions of positionality in the study of African Christianity, interdisciplinary methods and approaches and a number of case studies on political, social and ecological aspects of African Christian spirituality"--